HYPERAMYLASEMIA IN CHRONIC RENAL FAILURE-A COMPARATIVE STUDY - DR. CH.KALAVATHI,; DR.A.BHAGYALAKSHMI, (International Journal of Pharma and Bio Sciences, 2015)
Chronic renal failure results from progressive, irreversible destruction of nephrons. Gradual decline in Glomerular filtration rate(GFR),occurring over a period of years. Amylase concentration in serum is frequently found elevated in chronic renal insufficiency without associated pancreatic disease.The present study aims at measusuring the Amylase levels in Chronic renal failure patients&to note the effect of dialysis in S.Amylase levels.Materials&Methods: 50 patients admitted to the nephrology department with chronic renal failure constituted the study group.30 patients were on chronic maintainence haemodialysis.25 subjects without any evidence of renal pathology were taken as controls. S.Amylase,S.Creatinine, B.Urea was measured in controls &study group.Results: Amylase levels were studied &compared before and after dialysis.Mean values of all the parameters are raised in the study group compared to controls.Conclusion:Our study concludes that acute Pancreatitis can’t be diagnosed solely depending on the S.Amylase levels,because it is elevated in chronic renal failure also which may lead to false positive results.